Fabrication and characterisation of carbon fiber and CNT reinforced aluminium matrix composites - Rengarajan Karthic Narayanan. (2010)
Metal Matrix Composites (MMCs) are materials in which reinforcements are distributed in a metal matrix to create a material with properties that are different and generally superior to that of the metal alone. Among the metals available, aluminum (Al) is the most attractive matrix material due to its combination of low density, good corrosion resistance and excellent mechanical properties. The properties of AMCs can also be modified to meet the demands of different industrial applications by suitable combinations of matrix, reinforcement and processing route. This report is aimed to study the effect of adding carbon fiber and/or carbon nanotubes as reinforcement to the Al matrix composite microstructure and mechanical properties.